Sleep hygiene behaviours: An application of the theory of planned behaviour and the investigation of perceived autonomy support, past behaviour and response inhibition - Kor, K.; Mullan, Barbara (Routledge, 2011)
This study investigated the sleep hygiene behaviour of university students within the framework of the Theory of Planned Behaviour (TPB [Ajzen, I. (1991). The theory of planned behavior. Organizational Behavior and Human Decision Processes, 50, 179–211.]), and examined the predictive validity of additional variables including perceived autonomy support, past behaviour and response inhibition. A total of 257 undergraduate students from an Australian university were administered two online questionnaires at two time points. At time 1, participants completed the TPB questionnaire and the Go/NoGo task as a measure of response inhibition. A week later at time 2, participants completed a questionnaire measuring the performance of sleep hygiene behaviours. Multiple and hierarchical regression analyses showed that the TPB model significantly predicted intention and behaviour. Although intention and perceived behavioural control were statistically significant in predicting behaviour, past behaviour and response inhibition accounted for more variance when added to the TPB model. Subjective norm was found to be the strongest predictor of intention implying the importance of normative influences in sleep hygiene behaviours. Response inhibition was the strongest predictor of behaviour, reinforcing the argument that the performance of health protective behaviours requires self-regulatory ability. Therefore, interventions should be targeted at enhancing self-regulatory capacity.